Harnessing COVID-Driven Technical Innovations for Improved Multi-Disciplinary Cancer Care in the Post-COVID Era: The Virtual Patient Room. (6th October 2020) - Sim, Austin J.; Redler, Gage; Peacock, Jeffrey; Naso, Cristina; Wasserman, Stuart; McNitt, Khadija B.; Hoffe, Sarah E.; Johnstone, Peter A. S.; Harrison, Louis B.; Rosenberg, Stephen A.
Emergence of the COVID-19 crisis has catalyzed rapid paradigm shifts throughout medicine. Even after the initial wave of the virus subsides, a wholesale return to the prior status quo is not prudent. As a specialty that values the proper application of new technology, radiation oncology should strive to be at the forefront of harnessing telehealth as an important tool to further optimize patient care. We remain cognizant that telehealth cannot and should not be a comprehensive replacement for in-person patient visits because it is not a one for one replacement, dependent on the intention of the visit and patient preference. However, we envision the opportunity for the virtual patient "room" where multidisciplinary care may take place from every specialty. How we adapt is not an inevitability, but instead, an opportunity to shape the ideal image of our new normal through the choices that we make. We have made great strides toward genuine multidisciplinary patient-centered care, but the continued use of telehealth and virtual visits can bring us closer to optimally arranging the spokes of the provider team members around the central hub of the patient as we progress down the road through treatment.